Increasing R&D effectiveness researchers as business people - Purdon, William A. B.
William A. B. Purdon explains how market segment teams can overcome the insularity that often exists within the R&D function.
Market segment teams help guide a process that results in 'remarkable' new products and services in support of business objectives.
R&D is the critical source of continuous business regeneration and competitive advantage; however; regardless of how R&D is formally structured, an insularity tends to develop between it and the other functions that limits its ability to contribute to the corporate mission. Cross-functional Market Segment Teams, focused on the business's key market segments, provide the vehicle for the necessary "right interactions" and dialogue, within R&D and among the functions, that lead to on-going innovation. However, these interactions need to be designed in a way that allows the necessary strategic thinking to unfold. Moreover; no such progress can be made without an R&D leadership that is committed to change and will thus empower the R&D organization to act.
Keywords: R&D.